Indepth study of repeaters attending the Central Venereal Diseases Clinic, Colombo.. - Senanayake, M.D.H.K (My University, 1989)
This study was designed to identify the factors that lead to the process of acquiring repeated STD infections,and to identify the differences in demographic and behavioural characteristics between repeaters and non repeaters who attend the central VP clinic.